Green Empowerment: Strengthening Health Cadres through Family Medicinal Plants in Rural Communities - Rahmawati, Devira Eka; Kumalasari, Ana; Kasiami, Sri (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This started with a large number of people in Kenep Village who complained of minor illnesses, plus lack of knowledge and lack of public awareness of health made the problem even more complex. Therefore, this research aims to provide an overview of community empowerment by developing Family Medicinal Plants (TOGA) cadres to improve health in Kenep Village, Balen, and Bojonegoro. This research used a qualitative research method with a descriptive approach. Data collection techniques were carried out using observation, interviews, and documentation. The research focuses on community empowerment theory, which includes principles of equality, participation, sustainability, and self-reliance. The research results show that the development of TOGA cadres increases public knowledge and health awareness. Based on indicators of the ten most common diseases in 2021, 500 suffering from mild illnesses will decrease to 157 in 2022. This indicates a decrease in minor illnesses since the TOGA cadre empowerment program was implemented. Apart from that, the community also succeeded in innovating various processed products from TOGA, which can increase the selling value of the product. So, this community empowerment for TOGA cadres in Kenep Village is going well and beneficial for TOGA cadres, especially in terms of increasing knowledge, health, and welfare.